Hydrogen storage properties of γ–Mg(BH4)2 modified by MoO3 and TiO2. (28th September 2015) - Saldan, I.; Frommen, C.; Llamas-Jansa, I.; Kalantzopoulos, G.N.; Hino, S.; Arstad, B.; Heyn, R.H.; Zavorotynska, O.; Deledda, S.; Sørby, M.H.; Fjellvåg, H.; Hauback, B.C.
Abstract The reversible hydrogen desorption–absorption of γ–Mg(BH4)2 ball milled with MoO3 and TiO2 has been investigated. No mechanochemical interaction between γ–Mg(BH4)2 and TiO2 was observed while for the 1:1 M ratio with MoO3, MoB2 was formed. There was little difference in the properties of γ–Mg(BH4)2 and γ–Mg(BH4)2 ball–milled with 0.02 mol percent TiO2 and MoO3. However, mixing in the same ratio γ–Mg(BH4)2 with TiO2 and MoO3 that had previously been subjected to high energy milling provided significant effects. For these materials, the DSC peaks appeared broader and were shifted to slightly lower temperatures, while the TPD peaks were decreased by ca. 20 °C, as compared to the pure γ–Mg(BH4)2. Faster hydrogen desorption kinetics was observed for the γ–Mg(BH4)2–MoO3 mixture. The reversible hydrogen storage capacity of γ–Mg(BH4)2–TiO2 at 271 °C was found to be 2.4 wt% H2 in the first cycle.